2019
DOI: 10.1021/acsomega.9b01463
|View full text |Cite
|
Sign up to set email alerts
|

Computational Peptidology Assisted by Conceptual Density Functional Theory for the Study of Five New Antifungal Tripeptides

Abstract: A well-behaved model chemistry previously validated for the study of the chemical reactivity of peptides was considered for the calculation of the molecular properties and structures of a group of five new antifungal tripeptides, namely (2 R )-2-[(2 S )-2-[(2 S )-2-amino-3-phenylpropanamido]propanamido]-5-[(diaminomethylidene)amino]pentanoic acid, (2 S )-2-[(2 S )-2-[(2 S )-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…As a follow up of previous research on the subject [41,42,43,44,45], this study sought to assess the chemical reactivity properties of the Papuamides family of marine peptides through the application of the Density Functional Theory concepts as well as the determination of their drug-likeness, bioactivity scores and pharmacokinetics based on the online Molinspiration program and on SwissADME, a free web tool for the evaluation of those properties [30,31,32,46,47,48].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…As a follow up of previous research on the subject [41,42,43,44,45], this study sought to assess the chemical reactivity properties of the Papuamides family of marine peptides through the application of the Density Functional Theory concepts as well as the determination of their drug-likeness, bioactivity scores and pharmacokinetics based on the online Molinspiration program and on SwissADME, a free web tool for the evaluation of those properties [30,31,32,46,47,48].…”
Section: Introductionmentioning
confidence: 83%
“…In the process of calculating the electronic properties for the chemical reactivity of the antimicrobial peptides involved the use of MN12SX/Def2TZVP/H2O model chemistry through the optimized molecular structures, as explained in detail in Section 3. The choice of this model chemistry was based in the fact that, according to our previous research [41,42,43,44,45], it allows obtaining HOMO (Highest Occupied Molecular Orbital) and LUMO (Lowest Unoccupied Molecular Orbital) energies that verify the KID procedure (Koopmans in DFT) making easier the determination of the chemical reactivity descriptors arising from Conceptual DFT.…”
Section: Computational Methodologymentioning
confidence: 99%
“…The resulting lowest energy conformers for each peptide obtained during this process were then reoptimized through the Density Functional Tight Binding (DFTBA) functionality accesible within the Gaussian 09 software [22]. By considering the experience acquired in the previous research of our group [11,[23][24][25][26][27][28][29][30], the model chemistry based on the association of the MN12SX functional with the Def2TZVP basis set using water as the solvent was con-sidered for the final optimization of the resulting molecular structures because it has been shown that it allows the verification of the 'Koopmans in DFT' (KID) procedure [11,[23][24][25][26][27][28][29][30]. In the same way, the process for the calculation of the electronic properties and the chemical reactivity descriptors of the fungal peptides involved the use of MN12SX/Def2TZVP/H2O model chemistry through the consideration of the previously optimized molecular structures.…”
Section: Computational Methodologymentioning
confidence: 99%
“…It has been shown by Frau and Glossman-Mitnik [11,[23][24][25][26][27][28][29][30] that the HOMO (Highest Occupied Molecular Orbital) and LUMO (Lowest Unoccupied Molecular Orbital) energies obtained with the MN12SX/Def2TZVP/H2O model chemistry allows the verification of the KID procedure, that is, rendering an approximate Koopmans behavior. With the aid of the KID technique and the finite difference approximation [11,[23][24][25][26][27][28][29][30], the following expressions can be used to define the global reactivity descriptors [14-16, 35, 36]: Electronegativity…”
Section: Calculation Of the Global Reactivity Descriptors Of The Amatmentioning
confidence: 99%
See 1 more Smart Citation